1966
DOI: 10.1111/j.1748-1716.1966.tb03313.x
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the Transport and Life‐Span of Amine Storage Granules in a Peripheral Adrenergic Neuron System1

Abstract: DAHLSTROM, A. and J. HAGGENDAL, Studies on the transport and life-span of amine storage granules in a peripheral adrenergic neuron system. Acta physiol. scand. 1966. 67. 2 78-288. The accumulation of noradrenaline (NA) above a ligation of the rat and cat sciatic nerve and the NA content of the adrenergic fibre system derived from this nerve were estimated. From the data obtained the rate of transport of amine storage granules and their life-span were calculated. For the rat the rate of transport was found … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
21
0

Year Published

1968
1968
1982
1982

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 258 publications
(24 citation statements)
references
References 15 publications
3
21
0
Order By: Relevance
“…2). Flow rates of 2.6 mm/hr (norepinephrine), 3.4 mm/hr (dopamine-,3-hydroxylase), and 1.9 mm/hr (tyrosine hydroxylase) were calculated by the method of Dahlstrom and Haggendahl (20), which assumes that the accumulation of norepinephrine, dopamine-,3-hydroxylase, and tyrosine hydroxylase activity is solely derived from axoplasmic transport.…”
Section: Resultsmentioning
confidence: 99%
“…2). Flow rates of 2.6 mm/hr (norepinephrine), 3.4 mm/hr (dopamine-,3-hydroxylase), and 1.9 mm/hr (tyrosine hydroxylase) were calculated by the method of Dahlstrom and Haggendahl (20), which assumes that the accumulation of norepinephrine, dopamine-,3-hydroxylase, and tyrosine hydroxylase activity is solely derived from axoplasmic transport.…”
Section: Resultsmentioning
confidence: 99%
“…Bittner & Kennedy (21) calculated how much membrane peripheral nerve terminals would need if they had to produce a new vesicle for each quantum discharged, and it seemed clearly beyond the realm of possibility. Dahlstrom & Haggendal (60) determined, from their measurements of the rate at which vesicles accumulate above axon ligatures, that the supply of new vesicles from the cell body to adrenergic neuromuscular junctions is far too slow to maintain the rate of transmitter discharge and turnover these terminals display. All these studies concluded that vesicle membrane must be conserved after transmitter discharge and reused.…”
Section: Recycling Of Synaptic Vesiclesmentioning
confidence: 99%
“…The amine granules are known to be transported distally to the nerve terminals by axoplasmic flow (Dahlstrom & Haggendal, 1966;Kapeller & Mayor, 1967;Laduron & Belpaire, 1968). Hence, this pattern of loss of catecho1amines from the area of the brain where the nerve cell bodies are located, with lesser reductions or even increases in concentration in the regions containing the nerve terminals, suggests to us that the intense activation caused by fighting may have accelerated the movement.of catecholamine-containing granules from the cell bodies where they are synthesized towards the nerve terminals where presumably the amines are released at an increased rate during periods of intense activation.…”
mentioning
confidence: 99%